The migration of musical film : from ethnic margins to American mainstream - Garcia, Desirée J., 1977- (Rutgers University Press, 2014)
"Movie musicals are among the most quintessentially American art forms, often celebrating mobility, self-expression, and the pursuit of one's dreams. But like America itself, the Hollywood musical draws from many distinct ethnic traditions. In this ... [book] ... Garcia examines the lesser-known folk musicals from early African American, Yiddish, and Mexican filmmakers, revealing how these were essential ingredients in the melting pot of the Hollywood musical ... [showing] how the folk musical was rooted in the challenges faced by immigrants and migrants who had to adapt to new environments, balancing American individualism with family values and cultural traditions"--